Upper limb functionality and quality of life in women with five-year survival after breast cancer surgery Funcionalidade do membro superior e qualidade de vida em pacientes com sobrevida de cinco anos após tratamento cirúrgico para câncer de mama - Recchia T.L.* (2017)
© 2017 by Thieme-Revinter Publicações Ltda, Rio de Janeiro, Brazil.Objective To evaluate the correlation between upper limb functionality and quality of life in women with five-year survival following breast cancer surgical treatment. The secondary objective was to evaluate the function of the ipsilateral upper limb and the quality of life in relation to the type of surgery and the presence of pain. Methods The Disabilities of Arm, Shoulder and Hand (DASH), and the Functional Assessment of Cancer Therapy-Breast plus Arm Morbidity (FACTB + 4) questionnaires were used to evaluate upper limb function and quality of life respectively. Data distribution was verified by the Shapiro-Wilk test. Pearson’s correlation coefficient was used for the parametric variables, and Spearman’s rank correlation coefficient was used for the distribution of non-parametric variables. The statistical significance was set at 5% (p < 0.05). Results The study included 30 patients, with a mean age of 51.23 (±8.72) years. The most common complications were: Pain (50%), adherence (33.3%), and nerve lesion (20.0%). There was a moderate negative correlation between the instruments DASH and FACTB + 4 (total score), r =-0.634, and a strong negative correlation between the DASH and the FACTB + 4 armsubscale, r =-0.829. The scores of both questionnaires showed significant difference on the manifestation of pain. However, there was no significant difference found when comparing the scores considering the type of surgery performed. Conclusions Five years after surgery, the patients showed regular functionality levels on the ipsilateral upper limb and decreased quality of life, especially in the group manifesting pain.